Transformed Follicular Lymphoma (TFL) Predicts Outcome in Advanced Endometrial Cancer - Wakahashi, Senn; Kawakami, Fumi; Wakahashi, Kanako; Minagawa, Kentaro; Matsuo, Keitaro; Katayama, Yoshio; Yamada, Hideto; Matsui, Toshimitsu; Sudo, Tamotsu (Cancer epidemiology, biomarkers & prevention, 2018)
Background: Transformed follicular lymphoma (TFL, ZC3H12D) was identified as a candidate tumor suppressor gene that contributes to cell-cycle arrest through regulation of Rb phosphorylation, but the clinical impact of TFL is unknown. The goal of this study was to evaluate the prognostic significance of TFL expression in advanced endometrial cancer. Methods: Tissue samples were obtained from 103 patients with Federation Internationale des Gynaecologistes et Obstetristes stage III–IV endometrial cancer. Associations between TFL expression and outcomes were evaluated using the Kaplan–Meier method and multivariate Cox proportional hazards regression models. Results: There were 24 TFL-low cases (23.3%) and the 10-year progression-free survival (PFS) and overall survival (OS) in these cases were lower than those for patients with normal TFL expression in univariate analysis (PFS, P = 0.003; OS, P = 0.106). In multivariate analysis, TFL status was a significant predictor for PFS [HR = 2.76; 95% confidence interval (CI), 1.45–5.28; P = 0.002] and OS (HR = 1.94; 95% CI, 0.91–4.11; P = 0.085), adjusted for covariates. The TFL gene maps to human chromosome 6q25.1, where estrogen receptor alpha (ERα) gene ESR1 is also located. Lack of ERα expression is a poor prognostic factor in early endometrial cancer. Among 41 ERα-low patients, 10-year PFS was significantly lower in 15 TFL-low cases (univariate analysis, P = 0.055; multivariate analysis, HR = 4.70; 95% CI, 1.68–13.20; P = 0.003). Conclusions: We identified TFL as a strong independent prognostic factor, regardless of ERα status. Impact: An investigation of the mechanism underlying tumor suppression by TFL may lead to new therapies for patients with advanced endometrial cancer. Cancer Epidemiol Biomarkers Prev; 27(8); 963–9. ©2018 AACR.